COVID-19 risk factors amongst 14, 786 care home residents: an observational longitudinal analysis including daily community positive test rates of COVID-19, hospital stays and vaccination status in Wales (UK) between 1 September 2020 and 1 May 2021. (3rd May 2022) - Hollinghurst, Joe; Hollinghurst, Robyn; North, Laura; Mizen, Amy; Akbari, Ashley; Long, Sara; Lyons, Ronan A; Fry, Rich
Abstract: Background: COVID-19 vaccinations have been prioritised for high risk individuals. Aim: Determine individual-level risk factors for care home residents testing positive for SARS-CoV-2. Study design: Longitudinal observational cohort study using individual-level linked data from the Secure Anonymised Information Linkage (SAIL) databank. Setting: Fourteen thousand seven hundred and eighty-six older care home residents (aged 65+) living in Wales between 1 September 2020 and 1 May 2021. Our dataset consisted of 2, 613, 341 individual-level daily observations within 697 care homes. Methods: We estimated odds ratios (ORs [95% confidence interval]) using multilevel logistic regression models. Our outcome of interest was a positive SARS-CoV-2 PCR test. We included time-dependent covariates for the estimated community positive test rate of COVID-19, hospital inpatient status, vaccination status and frailty. Additional covariates were included for age, sex and specialist care home services. Results: The multivariable regression model indicated an increase in age (OR 1.01 [1.00, 1.01] per year), community positive test rate (OR 1.13 [1.12, 1.13] per percent increase), hospital inpatients (OR 7.40 [6.54, 8.36]), and residents in care homes with non-specialist dementia care (OR 1.42 [1.01, 1.99]) had an increased odds of a positive test. Having a positive test prior to the observation period (OR 0.58 [0.49, 0.68]) and either one or two doses of a vaccine (0.21 [0.17, 0.25] and 0.05 [0.02, 0.09], respectively) were associated with a decreased odds. Conclusions: Care providers need to remain vigilant despite the vaccination rollout, and extra precautions should be taken when caring for the most vulnerable. Minimising potential COVID-19 infection for care home residents when admitted to hospital should be prioritised.